DESIGNING THE COLLABORATIVE PLATFORM MEANT TO INCREASE ORGANISATIONAL COMPETITIVENESS IN AGROFOOD RESEARCH - Nedita, Gabriela; Stoian, Mirela; Rădulescu, Anca Elena (Economics of Agriculture, 2018)
This paper presents the premises and coordinates of realizing a collaborative platform meant to increase organizational competitiveness and knowledge management, expertise and partnerships in agro food research and development. The web collaborative platform may be accessed by organizations who are partners and it has as purpose to use at high levels the intangible resources of the research and innovation community, respectively to accelerate the process of innovation. The platform ensure building a network of information and knowledge in electronic format, in order to optimize time and costs of accessing information, to reduce the impact of personnel who work in research migration, young researchers integration into the system, the possibility to interconnect the network to other similar networks of the outsiders communities of research.